Perempuan Dan Fenomena Kekerasan Berbasis Gender Online Dalam Media Sosial - Fidella Azhar Julian; Wa Ode Asmawati (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2024)
Online gender-based violence against women is a social phenomenon that is increasingly common. Online gender-based violence against women takes advantage of technological developments and the use of social media. The aim of this research is to provide an overview of women's lives in the shadow of the phenomenon of online gender-based violence. The method used in this research is a quantitative descriptive approach involving female students from the Faculty of Social and Political Sciences, Muhammadiyah University, Jakarta, academic year 2019 – 2020 as respondents. The method for determining respondents in this research is non-probability sampling - purposive. If we look at the current situation, gender-based violence has occurred in all walks of life, such as household life, society and in the political arena. Based on the grouping of types of platforms that are popularly used and have a high potential for online gender-based violence, namely Whatsapp and Instagram. If we look at the respondents' understanding of online gender-based violence, there are still respondents who do not really understand this social phenomenon. The most common cause of gender-based violence against women is low tolerance towards the opposite sex and knowledge about gender equality. This online gender-based violence has a broad impact, equivalent to the impact of gender-based violence that occurs conventionally, victims will experience emotional, psychological and social losses.